Autoimmune hemolytic anemia and thrombocytopenia attributed to an intrauterine contraceptive device. Issue 3 (11th September 2014) - Khawandanah, Mohamad O.; Weiss, Susan M.; Cherry, Mohamad A.; Maymani, Hossein; Selby, George B.; Aster, Richard H.; George, James N.; Holter Chakrabarty, Jennifer L.
<x xml:space="preserve">Abstract</x> Background Evans syndrome is a rare condition manifested by combined autoimmune hemolytic anemia (AIHA) and thrombocytopenia or neutropenia. It is often associated with other autoimmune disorders, immunodeficiencies, and non‐Hodgkin's lymphoma. Case Report We describe a patient with Evans syndrome that may have been related to exposure to a polyethylene‐based intrauterine contraceptive device (IUD). A 26‐year‐old white female presented with severe, symptomatic AIHA and subsequently developed severe thrombocytopenia. She had a refractory course resistant to multiple treatments including corticosteroids, intravenous immune globulin, rituximab, splenectomy, cyclophosphamide, cyclosporine, eculizumab, and plasma exchange. It was then noticed that her serum autoantibody agglutinated red blood cells (RBCs) in the presence of polyethylene glycol (PEG) but not in the absence of PEG nor when an alternative agglutination enhancing technique, low‐ionic‐strength solution, was used. Therefore, her polyethylene‐containing IUD, which was a polyethylene frame with a levonorgestrel‐releasing device, was removed. Norgestrel‐dependent, platelet (PLT)‐reactive antibodies were not identified by either flow cytometry or in vivo in a NOD/SCID mouse. Testing for PEG‐dependent antibodies was not possible. Remission, with no requirement for RBC or PLT transfusions and return of her hemoglobin and PLT counts to normal, followed removal of the IUD. Conclusion The patient's recovery after removal of the IUD and the PEG dependence of RBC agglutination suggested a possibility that the IUD may have been a contributing factor to the etiology of Evans syndrome in this patient.